KC-PLM: Knowledge collaborative product lifecycle management - Ferreira, J. (Handbook of research on social dimensions of semantic technologies and web services, 2009)
This chapter defines a system and a methodology, the Knowledge Collaborative Product Lifecycle Management (KC-PLM) to better support the complete product lifecycle in the industry. The KC-PLM system intends to reduce the lead-time from new product development to production by providing and integrating knowledge platform, based on a semantic information repository, domain ontology, a domain specific language and on the user collaboration. These characteristics differentiate the KC-PLM system from others PLM systems, because it supports an intelligent rules engine, to extrapolate and make inference with historical solutions that allow the generation of new solutions. A real case study in automobile business shows the current proposal application and its benefits in a product concept phase.